Caffeine and EGCG Alleviate High-Trans Fatty Acid and High-Carbohydrate Diet-Induced NASH in Mice: Commonality and Specificity - Xin, Xin; Cheng, Chen; Bei-yu, Cai; Hong-shan, Li; Hua-jie, Tian; Xin, Wang; Zi-ming, An; Qin-mei, Sun; Yi-yang, Hu; Qin, Feng (Frontiers in Nutrition, 2021)
Caffeine and epigallocatechin-3-gallate (EGCG), which respectively are the major functional extract from coffee and green tee presenting protective effects against non-alcoholic fatty liver diseases (NAFLD). Even these two beverages and their functional extracts are highly recommended as potential treatment for overweight and NAFLD in clinic, the pharmacodynamic effects and pharmacological mechanisms of them on nonalcoholic steatohepatitis (NASH) still keep unclear. Therefore, this study is aiming to explore the commonality and specificity of the pharmacodynamic effects and pharmacological mechanisms of caffeine and EGCG on NASH mice, which were fed with a high-trans fatty acid/high-carbohydrate diet (HFHC) for 30 weeks in total. C57BL/6J mice were fed a normal diet (control group) or a HFHC diet (NASH group) separately for 24 weeks. HFHC group mice were additionally treated with caffeine (75 mg/kg) or EGCG (100 mg/kg) for 6 weeks, obeticholic acid (10 mg/kg) as a control group. The pharmacological effects of the drugs, including on glucose and lipid metabolism, liver inflammation and fibrosis were evaluated. Gene expression in liver tissue samples from the different groups was assessed. Both caffeine and EGCG significantly reduced the liver manifestations of NASH induced by HFHC. The pathological aspects of liver lipid deposition, inflammation, and liver fibrosis in two groups both were strongly ameliorated. Of note, most indexes were stronger reversed in the caffeine group, although AST activity, fasting blood glucose, and the HOMA-IR were more improved in the ECGC group. There were 714 differentially expressed genes between the caffeine and HFHC groups and 268 differentially expressed genes between the EGCG and HFHC groups. Twenty and 17 NASH-related KEGG signaling pathways were enriched by caffeine and EGCG, respectively. This study confirmed that 75 mg/kg caffeine and 100 mg/kg EGCG could significantly improve liver lipid deposition, glucose metabolism, inflammation, and fibrosis in a mouse model of NASH induced by HFHC. The bioinformatics platform we built for caffeine and EGCG in NASH disease found that two drugs may greatly overlap in improving the mechanism related to NASH inflammation, but caffeine may have better potential in regulating glucose metabolism and EGCG may have better potential in regulating lipid metabolism.